2012
DOI: 10.5539/gjhs.v5n2p13
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Dietary Supplements on the Quality of Life of Retired Professional Football Players

Abstract: Professional football players may experience negative health consequences when they retire such as chronic pain, cognitive problems as well as other consequences of sports-related injuries. The purpose of this pilot study is to determine the effects of dietary supplementation with multiple nutrients on the quality of life of retired football players. Fifteen retired players received daily supplementation of fish oil with cholecalciferol, antioxidants, natural vitamins and minerals, polysaccharides and phytoste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…2013 regarding the effect of the nutritional supplements on the quality of life among the retired professional football players showed that the use of fish oil, antioxidants, vitamins, and natural minerals on a daily basis can bring about improvements in the physical and psychological dimensions of the quality of the individuals' lives upon the completion of the intervention. [ 21 ] However, the results and effects of using supplements are different on the quality of the old people's lives. In some of the studies, the effect of supplements and vitamins' use on the strengthening of the old people's physiques has been shown.…”
Section: Introductionmentioning
confidence: 99%
“…2013 regarding the effect of the nutritional supplements on the quality of life among the retired professional football players showed that the use of fish oil, antioxidants, vitamins, and natural minerals on a daily basis can bring about improvements in the physical and psychological dimensions of the quality of the individuals' lives upon the completion of the intervention. [ 21 ] However, the results and effects of using supplements are different on the quality of the old people's lives. In some of the studies, the effect of supplements and vitamins' use on the strengthening of the old people's physiques has been shown.…”
Section: Introductionmentioning
confidence: 99%
“…In controlled human trials, polysaccharide intake enhanced the immune system biomarkers in the blood of healthy adults [ 22 ]. The effect of dietary supplements with polysaccharides on retired professional football players supported and optimized their quality of life [ 25 ]. However, no data regarding the impact of AA supplementation on healthy marathon runners performing strenuous physical activity is available.…”
Section: Introductionmentioning
confidence: 99%
“…The same study has proven that this is a good manner of improving modifiable cardiovascular risk factors related to lipid levels in professional football players. [40,41] Machado P. et al have researched the effects of omega-3 fatty acids diet supplementation on the plasmatic lipid profile of swimmers in the time span before a competition. In this direction they have used fish oil (containing a total of 950 mg EPA and 500 mg DHA) in the form of capsules, meaning 2.5 g/day, for 45 days before the competition.…”
Section: Introductionmentioning
confidence: 99%